Discourse-voice regulatory strategies in the psychotherapeutic interaction: a state-space dynamics analysis - Tomicic, Alemka; Martínez, Claudio; Pérez, J. Carola; Hollenstein, Tom; Angulo, Salvador; Gerstmann, Adam; Barroux, Isabelle; Krause, Mariane (Frontiers in Psychology, 2015)
This study seeks to provide evidence of the dynamics associated with the configurations of discourse-voice regulatory strategies in patient-therapist interactions in relevant episodes within psychotherapeutic sessions. Its central assumption is that discourses manifest themselves differently in terms of their prosodic characteristics according to their regulatory functions in a system of interactions. The association between discourse and vocal quality in patients and therapists was analyzed in a sample of 153 relevant episodes taken from 164 sessions of five psychotherapies using the State Space Grid (SSG) method, a graphical tool based on the Dynamic Systems Theory (DST). The results showed eight recurrent and stable discourse-voice regulatory strategies of the patients and three of the therapists. Also, four specific groups of these discourse-voice strategies were identified. The latter were interpreted as regulatory configurations, that is to say, as emergent self-organized groups of discourse-voice regulatory strategies constituting specific interactional systems. Both regulatory strategies and their configurations differed between two types of relevant episodes: Change Episodes and Rupture Episodes. As a whole, these results support the assumption that speaking and listening, as dimensions of the interaction that takes place during therapeutic conversation, occur at different levels. The study not only shows that these dimensions are dependent on each other, but also that they function as a complex and dynamic whole in therapeutic dialogue, generating relational offers which allow the patient and the therapist to regulate each other and shape the psychotherapeutic process that characterizes each type of relevant episode.